Vitality attributes and their associations with intrinsic capacity, resilience, and happiness in community-dwelling adults: Results from Gan-Dau Healthy Longevity Plan Wave 2 - Kuan-Yu Peng; Zhi-Jun Chen; Fong-Ping Tang; Shu-Chiung Lee; Heng-Hsin Tung; Katelyn E. Chen; Liang-Kung Chen; Fei-Yuan Hsiao (The Journal of Nutrition, Health and Aging, 2025)
Background: Vitality is a key domain of intrinsic capacity (IC) in healthy aging, but its measurement and relationships with other domains of IC and psychosocial constructs of well-being remain understudied. This study examined associations between different vitality attributes and other domains of IC as well as psychosocial constructs including resilience and happiness in middle aged and older adults, as these associations were fundamental for establishing evidence-based interventions to promote healthy aging. Methods: This cross-sectional analysis included 981 participants (75.0% female and 49.2% aged between 65−74 years) from the Gan-Dau Healthy Longevity Plan wave 2 cohort. We assessed four vitality attributes: nutritional status (self-reported appetite loss, self-reported weight loss, Mini Nutritional Assessment-Short Form (MNA-SF)), energy (self-perceived fatigue), neuromuscular function (low grip strength, defined by the Asian Working Group for Sarcopenia (AWGS) 2019 criteria), and circulating biomarkers of metabolism (elevated C-reactive protein (CRP)>0.5 mg/dL). Other IC domains were assessed based on the WHO ICOPE concept and existing literature. Psychosocial constructs were evaluated using the Brief Resilience Scale and Chinese Happiness Inventory. Comparisons of demographics and distribution of vitality attributes were performed with the chi-square or Fisher’s tests for categorical variables and t-tests for continuous variables when appropriate. Multivariate logistic regression models and generalized linear models (GLMs) were used to investigate the association between impairments in different vitality attributes and other IC domains as well as psychosocial constructs, respectively. Results: Among vitality attributes, low grip strength was most prevalent (38.2%), followed by suboptimal nutritional status measured by MNA-SF (15.4%), and self-perceived fatigue (6.7%). Low grip strength was significantly associated with locomotion impairment (adjusted OR 1.70 [95% CI 1.25−2.31], p = 0.001) and psychological impairment (1.85 [1.26−2.73], p = 0.002). Although relatively uncommon, self-perceived fatigue also showed strong associations with impairments in locomotion (2.47 [1.44−4.23], p = 0.001) and psychological domains (8.34 [4.83−14.37], p < 0.001). All vitality attributes except self-reported weight loss and elevated CRP significantly correlated with psychosocial constructs. Conclusions: Our findings demonstrate that low grip strength, suboptimal nutritional status and energy as vitality attributes showed strong link to other IC domains (mainly locomotion and psychological) as well as psychosocial constructs. This finding highlights the heterogeneity of the vitality domain for which it might not be evaluated by a single attribute only but by a combination. Importantly, social factors were strongly associated with vitality impairments, emphasizing the critical role of social determinants in IC assessment.